CAREER EDUCATION IN A GENERAL EDUCATION SCHOOL: CAREER EXPECTATIONS OF SENIOR FORM PUPILS - Jegelevičienė, Violeta; Merfeldaitė, Odeta; Railienė, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Career education is to be analysed as the factor of lifelong learning which promotes engagement, the adaption of labour force to the conditions of the market, entrepreneurship. It is the process of the acquisition and development of career competences which enables a person to manage his career. appropriate career choices, which have been made, have a great influence over person‘s successful socialisation. Career expectations, their analysis is a part of career planning which is oriented towards the formation of short-term and long-term career objectives. The article analyses the career expectations of senior pupils in the context of career education. The analysis of the theoretical concept of career expectations in the context of career education is presented and the analysis of the results of the quantitative study, which reveals career expectations of senior pupils, is introduced. The results of the study reveal the approach of senior pupils to their career and career expectations. The analysis of the study findings revealed that: senior pupils perceive a career in the context of contemporary career concept: as self-realisation, personal development, the sequence of learning and work experiences during life; after leaving school, further studies in the institutions of higher education are still the most popular choice; an extremely important factor of a good job and a successful career is also the reconciliation of hobbies and a job, and an opportunity to get engaged in an activity they enjoy; the respondents have career expectations not only with regard to personal development and honest assessment, but also working environment.